The Sabra : the creation of the new Jew - Almog, Oz (S. Mark Taper Foundation imprint in Jewish studies., 2000)
This book provides a comprehensive portrait of the Sabras (the state of Israeli's first generation, born between the 1930's and 40's) recreating their life, their thought, and their role in Jewish history.